Implementation of PjBl Model in Biotechonology using Traditional Project of Betung Bamboo Shoot Pekasam at Senior High Scholl Bonti District - Entin Daningsih; Putri Sekarayu; Asriah Nurdini Mardiyyaningsih (Postgraduate, University of Mataram, 2026)
Project Based Learning (PjBL) is a student-centered learning model thaat emphasizes the production of a final product. However, the integration of local potential into project-based learning remains limited. The production of betung bamboo shoot (Dendrocalamus asper) pekasam is a traditional practice not widely recognized by students, despite its potential to extend shelf life and increase economic value. Therefore, incorporating bamboo shoot pekasam into PjBL can engage students in preserving local wisdom while fostering environmental awareness. The abundance of bamboo shoots in Bonti District presents a valuable local resource that can be developed into meaningful learning projects.This study aimed to determine students’ cognitive, affective, and psychomotor learning outcomes through a PjBL model based on betung bamboo shoots. The research employed a pre-experimental method with a One-Group Pretest-Posttest design. Instruments included lesson plans, pretest-posttest questions, LKPD, and validated assessment sheets using the Guttman scale. Data were analyzed using normality, homogeneity, and t-test. The results showed that the data were normally distributed and homogeneous. Cognitive scores increased from 54.26 to 78, while affective and psychomotor scores reached 84.6 and 90.02, both categorized as very good. These findings indicate that local potential-based PjBL effectively improves student learning outcomes.